Is Mobile Money Changing Rural Africa? Evidence from a Field Experiment - Catia Batista; Pedro C. Vicente (Institute of Labor Economics (IZA), 2023)
Rural areas in Sub-Saharan Africa are typically underserved by financial services. Mobile money brings a substantial reduction in the transaction costs of remittances. We follow the introduction of mobile money for the first time in rural villages of Mozambique using a randomized field experiment. We find that mobile money increased migration out of these villages, where we observe lower agricultural activity and investment. At the same time, remittances received and welfare of rural households increased, particularly when facing geo-referenced village-level floods and household-level idiosyncratic shocks. Our work suggests that mobile money can accelerate urbanization and structural change in Sub-Saharan Africa.
Keywords: O12; O15; O16; O33; G20; R23; 330; mobile money; migration; remittances; investment; agriculture; structural change; technology adoption; insurance; Mozambique; Africa